2022
DOI: 10.3390/ani12151977
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Intravenous Enoxaparin Administration in Feline Arterial Thromboembolism

Abstract: Induction of a hypocoagulable state is imperative in the treatment of feline arterial thromboembolism. Publications in human medicine report the use of enoxaparin intravenously in selected cases. The aim of our retrospective study was to report the regain of perfusion, short-term outcome, and complications of cats treated with a novel intravenous enoxaparin protocol (1 mg/kg bolus injection followed by 3 mg/kg/day continuous infusion) combined with oral clopidogrel administration. The secondary aim was to repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Dyspnea and panting may occur as a result of pain. The prognosis of this condition is cautiously considered, as a study reported that 61% of cats are euthanized when this condition first occurs, and the majority of cases are bilateral (78%) (Locquet et al, 2018;Mitropoulou et al, 2022;Vezzosi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Dyspnea and panting may occur as a result of pain. The prognosis of this condition is cautiously considered, as a study reported that 61% of cats are euthanized when this condition first occurs, and the majority of cases are bilateral (78%) (Locquet et al, 2018;Mitropoulou et al, 2022;Vezzosi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment can be pharmacological (MITROPOULOU et al, 2022), consisting of the dissolution of the thrombus and vascular surgery (VEZZOSI et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormally high levels of laboratory indicators are often registered in cats with ATE. Thus, in a retrospective study by Mitropoulou et al (2022), in animals hospitalised for arterial thromboembolism, hyperglycemia and high serum creatine phosphokinase activity were noted as the most common abnormalities.…”
Section: Introductionmentioning
confidence: 99%